Performance Review of Distillation Equipment Using An Evaporator - Imaniah Sriwijayasih; Sumardiono; Prativi Khilyatul Auliya (Proklamasi 45 University, 2024)
Aquadest is water from the result of distillation or what is usually called pure water. Aquadest water is water from distillation or what is usually called a process distillation. Aquadest, which is usually called aquadest, is not a water that is easy to find, because the price given is expensive and only used for one or even several specific things in particular chemistry practical activities. The purpose of this research is to review the evaporator and condenser in the distillation apparatus in order to obtain a product in the form of distilled water by examining the physical and chemical properties of distilled water. From the research that has been carried out it was concluded that the results of distilled water were of good quality in a distillation apparatus that is assembled with temperature and The optimum time is at a temperature of 100 C and 1 hour time, produces distilled water with levels TDS 9 mg/L, decent pH 6.12 used for practical purposes in laboratory